Radiation modified chitosan/polyvinyl alcohol film with polyvinyl pyrrolidone coating for heavy metal ion removal / Norhashidah Talip - Norhashidah , Talip (2020)
Chitosan (CS) / Polyvinyl Alcohol (PVA) films were obtained by solution casting method. To be used in the water treatment application, these film need to be improved in mechanical strength. In this study, 2% (w/v) chitosan and 5% (w/v) PVA were blend at different CS: PVA weight ratios (50:50, 70:30 and 90:10). These mixtures were then transformed into films by solution casting method. Mechanical properties of the films were evaluated using tensile strength test where, at 70:30 of CS: PVA ratio gave the best tensile strength. Therefore, this composition was selected to proceed with the radiation modification with Polyvinyl Pyrrolidone (PVP) coating. CS/PVA films were modified with layer of PVP and exposure to irradiation to improve its mechanical strength. The films were dipped into different concentrations of PVP solutions at 1%, 3% and 5% (w/v). They were then exposed to gamma radiation at 5,10,20 and 30 kGy. The tensile strength of CS/PVA films coated with 1% PVP was found to increase up to 31%. Elongation at break was improved by 1% PVP coating. Chemical structures of the films were obtained by Fourier transform infrared spectroscopy (FTIR). It showed that gamma irradiation might form crosslinking between the polymers chain. Morphology characteristic was done using scanning electron microscope (SEM) and Atomic force microscope (AFM). Surface morphology proved that by PVP coating and gamma irradiation increases the roughness of the films. Results obtained from SEM and X-ray diffraction (XRD) showed the compatibility between all the polymers used in this film. Adsorption capability of modified CS/PVA films towards copper (Cu) and lead (Pb) ions showed no significant different when compared with the original CS/PVA film. While for adsorption of zinc (Zn) ion, modified CS/PVA showed the amount of Zn ion adsorbed was increased at 1% PVP coating compared with unmodified CS/PVA films. Can be concluded that modification of CS/PVA film with gamma irradiation and PVP coating improved the mechanical strength of CS/PVA film and sustained the adsorption capability of the film towards heavy metals ion such as Cu, Pb and Zn ions. Therefore, this modification is suitable to be used in water treatment application towards heavy metals ion adsorption.